1982
DOI: 10.1029/gl009i005p00547
|View full text |Cite
|
Sign up to set email alerts
|

Influence of velocity shear on the Rayleigh‐Taylor instability

Abstract: The influence of a transverse velocity shear on the Rayleigh‐Taylor instability is investigated. It is found that a sheared velocity flow can substantially reduce the growth rate of the Rayleigh‐Taylor instability in the short wavelength regime (i.e., kL > 1 where L is the scale length of the density inhomogeneity), and causes the growth rate to maximize at kL < 1.0. Applications of this result to ionospheric phenomena [equatorial spread F (ESF) and ionospheric plasma clouds] are discussed. In particular, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1

Year Published

1983
1983
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 22 publications
4
42
1
Order By: Relevance
“…(6), do not accurately model the equatorial electrojet. However, based upon previous work (Guzdar et al, 1982;Hluba et al, 1983) and analysis of Eq. (14) using different plasma profiles, we find that the fundamental conclusion of this paper, viz., velocity shear can stabilize short wavelength modes of the gradient drift instability, Is not sensitive to the plasma profiles chosen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(6), do not accurately model the equatorial electrojet. However, based upon previous work (Guzdar et al, 1982;Hluba et al, 1983) and analysis of Eq. (14) using different plasma profiles, we find that the fundamental conclusion of this paper, viz., velocity shear can stabilize short wavelength modes of the gradient drift instability, Is not sensitive to the plasma profiles chosen.…”
Section: Discussionmentioning
confidence: 99%
“…First, studies of the Rayleigh-Taylor instability (Guzdar et al, 1982) and the Pedersen c'|trent driven gradient drift (or E x B) instability (Perkins and Doles, 1975; Juba *. L et al, 1983) indicate that velocity shear can have an i.portant effect on these instabilities.…”
Section: Manuscript Approved February 9 1983mentioning
confidence: 99%
“…Most of the research for nonlinear RT mode in the ionosphere has been restricted to collisional domain, although it has been shown that inertial effects are important in the high-latitude ionosphere. The influence of transverse velocity shear on Rayleigh-Taylor instability has been well investigated in the linear theory by various authors, especially, Guzdar, Satyanarayana, and their collaborators (Guzdar et al, 1982;Satyanarayana et al, 1987). They have found that a sheared velocity flow can substantially reduce the growth rate of a Rayleigh-Taylor instability in the short wavelength regime.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior has similarities with the growthrate observed by Guzdar et. al [16], where the competing effects were due to the KH and Rayleigh- …”
Section: B Second Velocity Profilementioning
confidence: 99%
“…al. [16] in 1982 found that velocity shear decreases the growth rate of the Rayleigh-Taylor mode and showed that unlike the static case, the most unstable wavenumber is finite. An analytic slab geometry calculation carried out by A.Hassam [17] demonstrated that velocity shear decreases the growth rate of the Rayleigh-Taylor instability and non-linearly positively stabilizes marginally stable profiles.…”
Section: Introductionmentioning
confidence: 99%